Phytochemical Screening And Thrombolytic Activity Of Chloroform Extract Of Urena Sinuata (l.) - Dibyajyoti S. . Swati P. (University of Eloued جامعة الوادي, 2014)
The present study was designed to investigate thrombolytic properties of chloroform extract of Urena sinuata along with phytochemical study for the presence of phytochemical constituents. The concentrated extracts were collected and allow to air dry for complete evaporation of chloroform. Phytochemical analyses were found to be positive for carbohydrates and gum, reducing sugar, alkaloid, steroid, glycoside and flavonoids. The percent clot lytic activity was compared with water (positive control) and standard enzyme streptokinase (negative control). The mean percent clot lytic activity of chloroform leaf extract of Urena sinuata was found 47.89%, which is significant compare with the positive and negative control. The present study suggests that chloroform extract of Urena sinuata has significant thrombolytic activity.
Articale in Journal of fundamental and Applied Sciences Vol. 06 N. 02
Keywords: Urena sinuate (L.); phytochemical; streptokinase; clot lytic activity.